Theoretical aspects of the sociological technology of studying family entrepreneurship - Andras, Iryna A.; Burova, Svetlana N. (Journal of the Belarusian State University. Sociology, 2019)
The article analyzes the theoretical foundations of a sociological study of the family as a subject of economic relations. The authors proceed from the fact that sociological technology is complex and includes the steps of identifying the most pressing problems of society, its theoretical analysis, empirical research and the development of practical recommendations for improving the situation in a particular social sphere. Family businesses are the foundation upon which many developed economies of the world hold. The authors consider foreign theories about the economic nature of the family, sociological approaches to family understanding by Soviet researchers, the revival of family entrepreneurship in the USSR and its current state in Belarus. Thus, a theoretical basis has been created for the development of a methodological section of the program for the empirical sociological study of the prospects for the development of family entrepreneurship in the Republic of Belarus.